Two types of strategies used by Japanese scientists, when writing research articles in English - Okamura, A. (System (Linköping), 2006)
In investigations of the second-language writing process the aim of interviews and questionnaires has often been to find shared difficulties among them. However, in practice some writers are more successful than others. The aim of this study is to examine how some writers succeed in mastering scientific discourse in English, in a non-English speaking environment. Interviews were conducted with 13 Japanese researchers: 5 junior, 5 middle-ranking and 3 established. The analysis focuses not only on their difficulties, but also on their strategies to cope with them. Findings show that identification of their audience may distinguish established researchers from others. Another distinguishing characteristic seems to be their learning strategies, and these can be divided into two sets. The first set focuses on reading academic texts in their field (subject knowledge-oriented) to learn typical writing patterns. This practice was adopted by all. The second involves giving direct attention to mastering English speakers’ language use (language-oriented strategies), but these were employed by only 2 junior and 3 established researchers. The majority seems to prefer simply to cope with their limited English, because of time constraints; however, efforts to adopt the second type would appear to pay off in the long run.